SOFT SKILL VS HARD SKILL DALAM DUNIA MARKETING: MANA YANG LEBIH PENTING BAGI MAHASISWA? - Zuhrinal M. Nawawi; Lathifah Ananda Putri (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
In this digital era, the marketing world has undergone rapid transformation, requiring skills beyond technical knowledge. This study aims to compare soft skills and hard skills in the context of marketing, and which is more important for students preparing for a career in this field. The method used is a literature review by analyzing various relevant sources discussing the importance of these two skills. The findings of the study show that while hard skills, such as proficiency in digital marketing tools and data analysis, remain important, soft skills, such as communication, teamwork, and adaptability, have a greater impact on success in marketing. This study also suggests that educational institutions should adopt a balanced approach in developing both skills to better prepare students for the increasingly competitive job market. Developing both soft and hard skills simultaneously can improve students' readiness for careers in the dynamic and rapidly changing marketing field.